Linac-Based THZ imaging at Chiang Mai university - Saisut J. (2015)
At the Plasma and Beam Physics Research Facility (PBP), Chiang Mai University, intense THz radiation is generated in a form of coherent transition radiation from femtosecond electron bunches. The THz radiation is used as a source of THz imaging system which was successfully setup and tested. The radiation is focused onto a sample which will be scanned using an xy-translation stage. The transmission or reflection at different points of the sample are recorded to construct a THz image. Details of the setup and the experimental results from the system will be presented. The THz imaging to accommodate a future IR-THz Free Electron Laser (FEL) will also be discussed. Copyright © 2012 by the respective authors.